Vous êtes sur la page 1sur 5

The Fourier transform

Luis Silvestre
June 7, 2013
In this note, we dene the Fourier transform and derive its main properties.
Note: When we say that a function f is integrable in R, we mean that
_
R
|f(x)| dx < +.
Optimally, this integral should be a Lebesgue integral, but those who are unfamiliar with Lebesgue integrals
can take these integrals to be Riemann integrals as well. The only problem of using Riemann integration
instead of Lebesgue integration is in the application of some subtle limit theorems or in the justication of
a change in the order of integration. These justications are pointed out in the end of some proofs (when
necessary). Those unfamiliar with Lebesgue integration should skip these little notes and just believe the
limits and integrals work as expected.
1 Introduction
In a previous note, we explored the Fourier series, which allowed us to write an L-periodic function in an
interval as an innite sum of trigonometric functions:
f(x) =

kZ
a
k
e
2i(k/L)x
.
Here L is the length of the period, and k ranges among all integers. Note that as L , the values of k/L
form a thinner mesh in R.
The Fourier transform is a version of the same construction but for functions dened in the whole real
line which are not assumed to be periodic. It can be understood formally as a limit of the Fourier series as
the length of the period L goes to innity and the possible values of k/L become a continuum of values.
This limit process as L is explained in fair detail below, however, it seems more convenient to dene
the Fourier transform guessing the formula from analogy with the formulas for Fourier series, and prove all
its properties directly from the formula.
Given f : R C, we dene its Fourier transform

f by the formula

f() =
_
R
f(x)e
2ix
dx.
We also dene the inverse-Fourier transform g by
g(x) =
_
R
g()e
2ix
d.
Our main objective will be to prove that

f(x) = f(x).
Note that the denitions make sense as long as f and g are integrable functions on R. However, for some
proofs it will be convenient to make stronger regularity assumptions.
1
1.1 Obtaining the Fourier transform as a limit of Fourier series as L
We start by pointing out that this section can be skipped safely and in fact we recommend you to do so
unless you are really curious about this computation.
In this section we justify that

f = f with a non rigorous computation. Everything will be proved


rigorously in the later section. The hand-wavy computation in this section can be considered a motivation
for the denition of the Fourier transform.
Recall that the coecients a
k
in the Fourier series of an L-periodic function f are computed with the
formula
a
k
=
1
L
_
L/2
L/2
f(x)e
2i(k/L)x
dx.
And then f is recovered from a
k
by the series
f(x) =

kZ
a
k
e
2i(k/L)x
.
The same computation can be done with an arbitrary function f : R C. But then the Fourier series
will coincide with f only in the interval (L/2, L/2).
Suppose f is integrable in R. Let

f : R C be the Fourier transform.

f() =
_
R
f(x)e
2ix
dx.
Naturally, this function

f is exactly the following limit

f() = lim
L
La
L
,
where L must be taken to range among those values which make L Z. In other words, for large L, we
have that
a
k

1
L

f(k/L).
Therefore, for large L we should have
f(x)

kZ
1
L

f(k/L)e
2i(k/L)x
This last expression is nothing but a Riemann sum for the partition of R given by
k
= k/L, with

k
= 1/L. As L , the Riemann sum converges to the value of the integral.
lim
L

kZ
1
L

f(k/L)e
2i(k/L)x
=
_
R

f()e
2ix
dx
Thus, we nally obtained that by taking L , we get
f(x) =
_
R

f()e
2ix
dx.
2 Basic properties of the Fourier transform
Proposition 2.1. The Fourier transform satises the following basic properties.
1. Linearity: (f
1
+ f
2
)

=

f
1
+

f
2
and (g
1
+ g
2
)

= g
1
+ g
2
2. Translation: f( h)

() =

f()e
2ih
and g( h)

(x) = g(x)e
2ihx
3. Modulation:
_
f()e
2ih
_

() =

f( h) and
_
g()e
2ih
_

(x) = g(x h).


2
4. Scaling: (f(a))

() =
1
a

f
_

a
_
and (g(a))

(x) =
1
a
g
_
x
a
_
Here, we only assume that the functions f or g are integrable in R.
Note: where we write (f()e
2ih
) we mean the function H(x) = f(x)e
2ihx
. The same logic applies to other
uses of the dot notation.
The proof of all items in Proposition 2.1 follows from a simple computation using the denition of the
Fourier transform and inverse Fourier transform. We do only the last one here, and for the case of the
Fourier transform only. All the others are left as an exercise.
We write the formula for (f(a))

from the denition


(f(a))

() =
_
R
f(ax)e
2ix
dx,
Making the change of variables y = ax,
=
_
R
f(y)e
2i
y
a
dy
a
,
=
1
a
_
R
f(y)e
2i

a
y
dy =
1
a

f
_

a
_
.
The following properties are also useful. They will not be used to prove Theorem 3.4 (which says that

f = f), but they are very important for the applications of the Fourier transform.
We start with a semi-obvious statement.
Proposition 2.2. If f is integrable on R, then

f is a bounded function.
Proof. We observe that for any R,
|

f()| =

_
R
f(x)e
2ix
dx

_
R
|f(x)| dx.
Proposition 2.3. In the following, always assume that f and g are integrable in R.
If f is dierentiable and f

is integrable in R, then

f

() = 2i

f().
If xf(x) is integrable in R, then

f is dierentiable and (

f)

() = 2i(f())

().
If g is dierentiable and g

is integrable in R, then

g

(x) = 2ix g(x).


If g() is integrable in R, then g is dierentiable and ( g)

(x) = 2i(g())

(x).
Note that after we prove that

f = f one could argue that the rst item in the last proposition implies
all the others. In any case, the four items are proved using essentially the same computation based on an
integration by parts trick. We prove the rst one only, the other three are left as an exercise.
Proof. We write the denition of

f

(),

() =
_
R
f

(x)e
2ix
dx,
= lim
R
_
R
R
f

(x)e
2ix
dx,
We integrate by parts with du = f

(x) dx and v = e
2ix
,
= lim
R
f(R)e
2iR
f(R)e
2iR
+
_
R
R
f(x)2ie
2ix
dx,
3
Note that since f is integrable in R, then necessarily lim
R
f(x) = 0 at least up to subsequences. So we
can pass to the limit and get,
= 2i
_

f(x)e
2ix
dx,
= 2i

f().
In the previous proposition we can observe an interesting phenomena with the Fourier transform. We
see that the regularity of f is transformed into decay of

f and vice versa. For example, from Proposition
2.2, we see that if f is integrable, then

f is bounded. Combining this fact with Proposition 2.3, we see that
if f

is integrable then

f() C/|| for some constant C. Moreover, if f is k times dierentiable and f
(k)
is integrable in R, then

f() C/||
k
for some constant C. Thus, the more derivatives f has, the faster

f
decays at innity.
3 Inverse Fourier transform
We now prove that the special function G(x) = e
x
2
is the Fourier transform of itself.
Proposition 3.1. The function G(x) = e
x
2
satises

G() = G(). Also

G(x) = G(x).
Proof. We compute

G() =
_
R
G(x)e
2ix
dx,
=
_
R
e
x
2
2ix
dx,
=
_
R
e
(x+i)
2

2
dx = e

2
_
R
e
(x+i)
2
dx.
In order to complete the proof, we need to show that the last integral is equal to one. We use complex
analysis. Let R > 0 be a large number. Let be the path which goes straight from R + i to R + i,
then it follows down the segment to R, then it goes left to R and nally it closes the loop straight up to
R + i. Since the function h(z) = e
z
2
holomorphic, Cauchy theorem tells us that
0 =
_

h(z) dz
=
_
R
R
e
(x+i)
2
dx i
_

0
e
(R+iy)
2
dy
_
R
R
e
x
2
dx + i
_

0
e
(R+iy)
2
dy
The second and fourth integrals go to zero as R . This is because (R + iy)
2
as R
uniformly for y [0, ]. Therefore, e
(R+iy)
2
0 uniformly. Therefore, we can take limit as R to
obtain _
R
e
(x+i)
2
dx =
_
R
e
x
2
dx = 1.
The last identity is well known. It is usually the rst example we see when we study change of variables in
2D (using polar coordinates). This nishes the proof.
Corollary 3.2. The function g
a,x
() = e
2ix
G(a) satises
g
a,x
(y) =
1
a
G
_
y x
a
_
4
Proof. This is a combination of Proposition 3.1 with items 3 and 4 in Proposition 2.1.
The following proposition can be understood in a functional analysis context as that the Fourier transform
and the inverse Fourier transport are adjoint operators.
Proposition 3.3. Assume both |f| and |g| are integrable, then we have the identity
_
R

f()g() d =
_
R
f(x) g(x) dx.
Proof. For the proof it suces to write the denitions of the Fourier and inverse Fourier transforms and
change the order of integration
_
R

f()g() d =
_
R
__
R
f(x)e
2ix
dx
_
g() d
=
_
R
__
R
g()e
2ix
d
_
f(x) dx
=
_
R
g(x)f(x) dx
Note: the change in the order of integration is justied by Fubinis theorem since
__
RR

f(x)e
2ix
g()

dx d =
__
R
|f(x)| dx
___
R
|g()| d
_
< +.
The following result is the fact that

f = f. For now, we will assume that both f and



f are continuous
and integrable. We will see later that if f S, then both of these conditions are satised.
Theorem 3.4. Assume both f and

f are continuous and integrable. Then

f(x) = f(x).
Proof. We use the function g from Corollary 3.2 in Proposition 3.3. We have
_
R

f()g
a,x
() d =
_
R
f(y) g
a,x
(y) dy. (1)
Note that g
a,x
is a Gaussian centered at x and scaled by the factor a in a way that
_
R
g
a,x
= 1 for all a.
This is the same as the Heat kernel for t =

a. Recall (for example from our study of the heat equation)
that we have
_
R
f(y) g
a,x
(y) dy =
_
R
f(y)
1
a
G
_
y x
a
_
dy f(x) as a 0.
Thus, we can recover f(x) taking a 0 in (1). We then obtain
f(x) = lim
a0
_
R

f()g
a,x
() d = lim
a0
_
R

f()e
2ix
G(a) d =
_
R

f()e
2ix
d.
This nishes the proof of our theorem.
Note that the last identity is justied by the dominated convergence theorem given that we assume that |

f()|
is integrable.
Note that from Propositions 2.2 and 2.3, if f is integrable and twice dierentiable with f

integrable,
then

f is also integrable and Theorem 3.4 applies.
4 Parsevals identity (the Fourier transform in L
2
)
5 Applications to PDE
5